Pleiotropic Roles of CXCR4 in Wound Repair and Regeneration - Chen, Huating; Li, Gongchi; Liu, Yiqiong; Ji, Shuaifei; Li, Yan; Xiang, Jiangbing; Zhou, Laixian; Gao, Huanhuan; Zhang, Wenwen; Sun, Xiaoyan; Fu, Xiaobing; Li, Binghui (Frontiers in Immunology, 2021)
Wound healing is a multi-step process that includes multiple cellular events, such as cell proliferation, cell adhesion, and chemotactic response as well as cell apoptosis. Accumulating studies have documented the significance of the stromal cell-derived factor-1 (SDF-1) /CXCR4 signaling in the process of wound repair and regeneration. But the molecular mechanism of regeneration is not very clear. This review describes various types of tissue regeneration that CXCR4 participates in, and how the efficiency of regeneration is increased via CXCR4 overexpression. It will emphasize the pleiotropic effects of CXCR4 in regeneration at length. By delving into its specific molecular mechanisms, we hope to provide a theoretical basis for tissue engineering and future regenerative medicine.